Needs of Early Childhood Parents During Homeschooling the Covid Pandemic 19 - Ismaniar, Ismaniar; Wisroni, Wisroni; Hazizah, Nur (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
The School From Home (SFH) policy at the time of the Covid 19 outbreak now has a significant impact on various parties, especially early childhood and parents. The transfer of massive learning stimulation activities from school to home shows that not all parents are ready. This unpreparedness has a negative impact on both parents and children. There is a lot of data about the complaints of parents who are not able to provide optimal stimulation for their children, even to the appearance of words and actions that are out of control from parents which are very important for children, both physically and psychologically. The phenomenon of parents' unpreparedness requires assistance from various parties, especially academics and medical doctors. The participation of academics and educational education in sharing knowledge and skills will increase the readiness of parents in stimulating various aspects of AUD intelligence in the family environment. It is hoped that more and more academics will be able to improve the knowledge and skills of the community so that efforts to educate future creation in the future will be more easily realized.